Language of Advertising in Social- and Psycholinguistic - Маевская, Лина Дмитриевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article is devoted to the language of advertising which has a concrete aim, specific object and subject of research. Social and psychological character of a person makes us study effective cooperation in person and professional spheres. New information is transmitted to the society via language, in which new lexical units have appeared lately and they demonstrate realities of our life. As sublanguage of advertising can be named a laboratory of word-formation, so it is perspective as an object of research for linguistics. Innovations in language are new tendencies which characterize the vision of the world by modern society.